Low-grade Endometrial Stromal Sarcoma with Unusual Metastasis to the Skull - Araújo Júnior, Antonio Santos de; Arlant, Pedro Alberto; Salvestrini Júnior, Arnaldo; Fernandez, Angelo; Docema, Marcos Fernando de Lima; Mattedi, Rômulo Loss; Silveira, Thales Parenti; Caldas, José Guilherme Mendes Pereira; Fazzito, Mirella Martins (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Background Endometrial stromal sarcomas (ESSs) are the second most common uterine sarcomas. Although ESSs are often indolent, they have metastatic potential. To the best of our knowledge, there are only three reports of brain metastasis, and the present report is the first to describe a late skull metastasis of an ESS.Case Report We describe the case of a 51-year-old woman who presented abnormal vaginal bleeding 14 years ago; she was diagnosed with an uterine mass and submitted to a hysterectomy. One year ago she presented ESS lung metastasis followed by a left parietal calvarial metastasis. The optimal treatment for metastatic ESS is controversial, but the use of progesterone and aromatase inhibitors is advisable.
Keywords: endometrial stromal sarcoma; lung and skull metastases